Study on the mechanical and radiation-shielding properties of borided AISI 304 stainless steels - Çalik, Adnan (Materiali in tehnologije, 2013)
The boriding effect on the tensile properties, microhardness and radiation shielding has been studied. While boriding increased the hardness of the AISI 304 steel from 240 HV0.1 to the maximum value of 1 740 HV0.1, the elongation and the maximum stress clearly showed decreasing values. Borided specimens were more capable at stopping the high-energy photons and boriding improved the radiation-shielding properties of the AISI 304 steel. From the obtained results, it has been concluded that the borided AISI 304 stainless steel can be used as radiation shielding for g-rays.
Keywords: boriding; boriranje; radiation shielding; zaščita pred sevanjem; mechanical properties; mehanske lastnosti; nerjavno jeklo; stainless steel